Novel MIL-53(Fe)-encapsulated gelatinous boehmite granules and their enhanced photocatalytic performance towards tetracycline - Bui, Thi Minh Nguyet; Nguyen, Van Hung; Nguyen, Cao Duy An; Nguyen, Ngoc Bich; Vo, The Ky (Hue University Journal of Science: Natural Science, 2026)
Developing materials with high photocatalytic activity and easy recovery remains a challenge in industry. In this work, MIL-53(Fe) crystal powder was effectively encapsulated within gelatinous boehmite to produce millimetre-scale AlOOH@MIL-53(Fe) granules using the oil-drop method. The materials were utilised for the photodegradation of tetracycline (TC). These granules underwent detailed characterisation by SEM, FT-IR, XRD, N2 sorption, TGA, and UV-Vis DRS techniques. The resulting granular composites exhibited improved porosity and visible-light absorption. Photocatalytic testing under energy-efficient visible LED light demonstrated that the AlOOH@MIL-53(Fe) granules achieved a removal efficiency of 93% for TC, higher than that of the original MOF (82%) and the AlOOH granules without loaded MOF (54%). Kinetic analysis indicated that the photodegradation of TC followed a pseudo-second-order model, with rate constants in the following decreasing order: AlOOH@MIL-53(Fe) (0.0021 mg–1.L.min–1), MIL-53(Fe) (0.00074 mg–1.L.min–1), and AlOOH(0.00016 mg–1.L.min–1). Notably, the developed granules are easy to recover and retain suitable reusability in photocatalytic processes, highlighting their significant potential for real-world wastewater treatment applications.